PENGARUH QUENCHING DENGAN MEDIA PENDINGIN AIR DAN OLI TERHADAP MECHANICAL PROPERTIS BAJA S45C - Deni Setiadi; Achmad Kusairi Samlawi (Universitas Lambung Mangkurat, 2019)
The role of steel in the industrial world today is very important, especially in terms of making components related to violence such as gears, fly wheel, axe, and so forth.This steel has a high hardness for components that require hardness, to uletan and resistance to friction. get hardness and resistance to steel hence need heat treatment process using Quenching process. The material of this research is S45C carbon steel with specimen number 1 for hardness test before treatment and after treatment with rockwell test, this process is done in Central Laboratory of FMIPA UM, unfortunate. In this process heat treatment is carried out at temperatures of 800⁰C and 900⁰C with water and oil cooling medium, from the results of comparative analysis on S45C steel before and after the treatment obtained increased hardness. This can be seen from the test analysis in which 93 kgf of hardness n is for the untreated specimens. At a temperature of 800⁰C with a water cooling medium at a crude value of 94.6 kgf, and on oil cooling medium at a hardness value of 92.5 kgf. At a temperature of 900⁰C with a water cooling medium at a hardness value of 93.5 kgf and on the oil cooling medium at a value of 93 kgf. Can be concluded from all the cooling media is the highest media water with value of violence 94.6 kgf.Keywords: S45C Steel, Quenching, Cooling